Interactive Digital Storybook: ICT-Based Innovation in Learning the History of Islamic Culture - Sulastri; Nur Nasution, Wahyudin; Rakhmawati, Fibri (Sekolah Tinggi Ilmu Tarbiyah (STIT) Muhammadiyah Bangil in collaboration with Letiges & Association of Muslim Community in ASEAN (AMCA), 2024)
The main challenges in learning the history of Islamic culture include students' perceptions of being more enthusiastic, low student participation, limited teacher staff, and the need to use more ICT-based learning media. This research aims to make interactive digital storybooks a learning tool to deepen their understanding of the history of Islamic culture and create exciting and interactive learning resources that can increase student engagement and expand their knowledge about values, practices and essential events in Islamic culture. This type of research and development uses the ADDIE model (analysis, design, development, implementation and evaluation), with the research subjects being teachers and students of Madrasah Ibtidaiyah Swasta (MIS) Bhakti Mandiri Pematang Siantar, Medan, Indonesia. The results show that interactive digital storybooks significantly increase students' understanding and engagement in learning. However, it's worth being aware of some drawbacks, such as limited accessibility and potential technical issues. Nevertheless, interactive digital storybooks are still an adequate alternative in supporting students' learning about the history of Islamic culture. Limitations of this study include limited accessibility, potential technical problems and difficulties in navigating the interface in interactive digital storybooks. This research implies that interactive digital storybooks are an adequate alternative to support the learning of Islamic cultural history and have the potential to be improved by paying attention to factors such as suitability of content, pleasant design, and teacher involvement.